Глава 4. Доктринальні підходи до реалізаціїї цивільних процесуальних відносин у контексті вдосконалення законодавства про цивільне судочинство - Діденко, Лариса Василівна (Цивільний процес: теорія і практика. Концепції вчених з удосконалення законодавства про цивільне судочинство. Монографія, 2023)
The article is devoted to the analysis of doctrinal approaches to the implementation of civil procedural relations. The relevance of this issue is determined by the fact that many works were developed under significantly different conditions, which are significantly different from the current period, and some of the existing conclusions are ambiguous.It is noted that various problems of the functioning of civil procedural legal relations as a constituent element of the mechanism of civil procedural regulation are understudied.It is emphasized that the issue of legal relations is one of the fundamental ones in the theory of law, therefore there is a variety of concepts regarding its definition. It is proposed to understand civil procedural legal relations as dynamic and multi-stage individualized social relations, regulated by the norms of civil procedural law, arising between the court as a mandatory subject, persons participating in the case, and other participants in the civil process, and the connection between which are defined in their rights and obligations arising in civil proceedings for the purpose of ensuring justice in the protection of violated, unrecognized or disputed rights, freedoms or interests of natural persons, rights and interests of legal entities, interests of the state.The signs of legal relations as a special type of social relations are singled out: 1) emergence, termination or change only on the basis of legal norms that directly give rise to them; 2) the existence of mutual subjective rights and obligations of subjects of legal relations; 3) strong-willed character; 4) state protection; 5) individualization of subjects.The place and functions of civil procedural legal relations in the mechanism of civil procedural regulation are analyzed. It is indicated that the mechanism of civil procedural regulation is a system of complex, interconnected and united by a common goal of procedural and legal means, methods and forms that operate in a well-established manner and in constant connection and functioning of which is associated with the legal influence of the state on civil – legal relations aimed at satisfying the public and private interests of the participants and their regulation.It is proposed to divide the functions of civil procedural legal relations in the mechanism of civil procedural regulation into general theoretical functions of civil procedural legal relations and special sectoral functions of civil procedural legal relations.A conclusion was made regarding the optimization of the current civil procedural legislation by excluding from §3 Other participants in the legal process Chapter 4 Participants in the legal process of the Civil Procedure Code of Ukraine such a participant in the legal process as a witness.